(untitled) (Uzbek Scholar Journal, 2022)
Currently, patients in this article very definitely complain about the "craving" for heroin, vividly and in detail describe the attraction to the drug, ask for help, they are dominated by unconscious anxiety, vivid pictures of drug use appear in their dreams. Increased anxiety acted as the main and non-specific psychopathological marker of the general deterioration of the mental state. Withdrawal phobia was found in almost all clinical observations, depending on the dose of heroin used.